2008
DOI: 10.1177/003335490812300307
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Education: Still an Important Issue for Veterinarians

Abstract: Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) is a significant cause of immunosuppression that puts infected individuals at higher risk for developing severe complications from zoonotic infections and other animal-related hazards. The number of people living with HIV grows each year, assuring that veterinary practitioners will have clients and/or employees who are afflicted with HIV/AIDS. Veterinarians need to better understand HIV/AIDS for many reasons: to dispel unfounded belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Although pets can increase one's risk for additional infections, the positive mental health benefits of pet ownership were clearly described in our sample and have been supported in other research (Davis, 2008; Gosselink & Myllykangas, 2007; Vetter & Donnelly, 2006). Pet ownership can be encouraged by healthcare providers, but they must also ensure that women living with HIV/AIDS understand the importance of pet hygiene, along with their own symptom assessment and medication adherence.…”
Section: Discussionsupporting
confidence: 88%
“…Although pets can increase one's risk for additional infections, the positive mental health benefits of pet ownership were clearly described in our sample and have been supported in other research (Davis, 2008; Gosselink & Myllykangas, 2007; Vetter & Donnelly, 2006). Pet ownership can be encouraged by healthcare providers, but they must also ensure that women living with HIV/AIDS understand the importance of pet hygiene, along with their own symptom assessment and medication adherence.…”
Section: Discussionsupporting
confidence: 88%
“…These findings may be associated with actual prevalence of HIV infection or AIDS among respondent clientele but is more likely associated with HIV-and AIDS-related stigma and failure of people with HIV infection or AIDS to view veterinarians as a source of zoonotic disease information. 15 Veterinarians have received training on zoonoses, animal-related hazards, and the human-animal bond 11 and may provide a valuable source of information for people with HIV infection or and for physicians who treat patients with HIV infection or AIDS. Various approaches to encourage people with HIV infection or AIDS to use veterinarians as a resource for zoonoses information have been suggested and include display of educational material and signage in practices, comments in practice newsletters, and affiliation with HIV and AIDS support groups.…”
Section: Discussionmentioning
confidence: 99%
“…Louis Effort for AIDS, 2009). Second, physicians as well as veterinarians may wish to inquire if their HIV positive clients may have misconceptions about pet ownership and clarify them (Davis, 2008). Research has shown that the potential for transmission of infections from animals to HIV positive owners is low (Conti et al, 1995) and this needs to be more widely disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…Pets were noted to provide a source of conversation, to provide a health promoting routine by means of pet care and grooming activities, a reason for undertaking physical activity and a source of love. HIV-related studies have focused on the knowledge, attitudes and practices of physicians and veterinarians towards pet ownership among HIV positive persons (Davis, 2008; Hill, Petty, Erwin, & Souza, 2012) and on the effect of pet ownership on people living with HIV/AIDS (PLH/A).…”
mentioning
confidence: 99%